Synthesis of highly disperse tetragonal BaTiO3 nanoparticles with core–shell by a hydrothermal method*. Issue 4 (1st December 2017) - Li, Jinhui; Inukai, Koji; Tsuruta, Akihiro; Takahashi, Yosuke; Shin, Woosuck
Abstract: In order to synthesize of high-dispersion and tetragonal BaTiO3 (BT) nanoparticle, a hydrothermal method is used in a mixture of chloride metal sources and KOH with polyvinylpyrrolidone (PVP). The properties of BT–PVPs prepared by different reaction temperature and time are investigated via XRD, FE-SEM, DLS, FT-IR, and TEM to clarify the changes of the crystal phase, dispersion, and particle structure. The reaction is finished at 230 °C for 24 h and the critical reaction condition for that the crystal phase of the obtained BT particle changed from the cubic to the tetragonal is found to be 190 °C fixed in reaction time 24 h, and 9 h. During reaction the PVP on the BT surface decomposed to different form, and the PVP plays the role of dispersant in aqueous solution. By the hydrothermal condition of 230 °C for 24 h almost monodisperse BT–PVP with sizes of 83 nm and tetragonality (c/a) of 1.0062 were synthesized. The structure of nanoparticle, core (BT)–shell (PVP) was investigated by FT-IR and direct observed by TEM and the mechanism of particle growth and dispersion was discussed.